Analysis of Tourist Visit Decision to Tanjung Lesung - Ismail, Yunita; Sition, Lucky Jeremy (Journal of The Community Development in Asia, 2024)
Motivation is an important factor for prospective tourist in taking decisions about the destinations to be visited. The objectives of this study are to clarify and to know the influence of motivation, in variable escape motive, relaxation, enjoying natural resource and beautiful natural on tourists visiting decision to Tanjung Lesung. Population used in this research is the people that ever go to Tanjung Lesung for recreation, and sampling method used is convenient sampling. Number of samples is100 samples and questionnaire used to collect data. Data analysis method used is multiple regression analysis to know the influenced of independent variables toward dependent variable. The result find that, escape motive variable does not influenced significantly toward tourist visit decision, but variable relaxation, enjoying natural resource and beautiful natural are significance influenced toward tourist visit decision. Through the internet access already reach almost all area, people can not leave the daily responsibilities